Modified nano cerium oxide, thermoplastic resin modified material and preparation method thereof

By combining nano cerium oxide with specific ternary polymers, modified nano cerium oxide is prepared and blended with thermoplastic resins, the problem of insufficient mechanical properties of commercially available nano cerium oxide in automotive interior materials is solved, and the problem of significantly improved The physical properties of thermoplastic resin composites expand their application areas.

CN119219981APending Publication Date: 2024-12-31HEFEI GENIUS NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310773789.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Commercially available nano cerium oxides are difficult to meet the requirements of mechanical properties in automotive interior materials, resulting in limited application of thermoplastic resin composites.

Method used

Using a preparation method for modified nano cerium oxide, the modified nano cerium oxide is formed by combining trifluoroethyl methacrylate-glycidyl methacrylate-bisphenol A epoxy diacrylate terpolymer Nano cerium oxide and blend it with thermoplastic resin to improve the physical properties of the material.

Benefits of technology

The tensile strength, flexural modulus and impact strength of thermoplastic resin composites have been significantly improved, expanding its application areas, showing better physical properties than commercially available nano cerium oxide modified thermoplastic resins.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides modified nano cerium oxide, a thermoplastic resin modified material and a preparation method of the modified nano cerium oxide. The preparation method of the modified nano cerium oxide comprises the following steps: stirring nano cerium oxide, a terpolymer and a catalyst to react to obtain a solution D; stirring and reacting the solution D and N, N-dimethylformamide at normal temperature to obtain a solution E; and filtering, washing and drying to obtain the modified nano cerium oxide. According to the invention, the trifluoroethyl methacrylate-glycidyl methacrylate-bisphenol A epoxy diacrylate ternary polymer is used for modifying the surface of the nano CeO2, the average particle size of the prepared modified nano CeO2 is very small, and agglomeration of the nano CeO2 is effectively prevented; the compatibility of the nano CeO2 and the thermoplastic resin matrix and the dispersity of the nano CeO2 in the thermoplastic resin matrix are improved, and the mechanical property of the thermoplastic resin modified material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a modified nano cerium oxide, a thermoplastic resin modified material and a preparation method thereof. Background Art

[0002] Nano cerium oxide (CeO2) has high chemical stability. Adding it to thermoplastic resin can greatly improve the mechanical properties of thermoplastic resin composite materials. However, in some automotive interior material application areas, it is difficult to meet the requirements of mechanical properties (tensile strength, impact strength, flexural modulus) of automotive interior materials by simply using commercially available nano cerium oxide to modify thermoplastic resin.

[0003] For this reason, the present invention synthesizes a self-made modified nano-CeO2 to modify thermoplastic resin, which has better physical properties than directly modifying thermoplastic resin with commercially available nano-cerium oxide. Related literature has not been reported, which greatly expands the application field of thermoplastic resin composite materials and has very practical significance. Summary of the invention

[0004] The purpose of the present invention is to provide a modified nano cerium oxide, a thermoplastic resin modified material and a preparation method thereof, which can improve the physical properties of thermoplastic resin composite materials.

[0005] The first object of the present invention is to provide a method for preparing modified nano-cerium oxide, which comprises the following steps:

[0006] (1) stirring and reacting nano-cerium oxide, a terpolymer and a catalyst to obtain a solution D, wherein the terpolymer is a terpolymer of trifluoroethyl methacrylate-glycidyl methacrylate-bisphenol A epoxy diacrylate;

[0007] (2) stirring solution D and N,N-dimethylformamide at room temperature to obtain solution E;

[0008] (3) Filter, wash and dry the solution E to obtain modified nano-cerium oxide.

[0009] In a further embodiment, in step (1), the mass ratio of the nano-cerium oxide, the terpolymer and the catalyst is (80-100): (2-6): (0.2-0.4).

[0010] The catalyst is potassium sulfate and triethylamine, and the mass ratio of the two is 1:1; the stirring reaction temperature is 40-60°C and the time is 6-8h.

[0011] In a further embodiment, in step (2), the mass ratio of the solution D to N,N-dimethylformamide is (30-40):(80-100); and the stirring reaction time is 1-3 hours.

[0012] The drying in step (3) refers to drying in an oven at 60-80°C for 2-4 hours.

[0013] In a further embodiment, the preparation steps of the trifluoroethyl methacrylate-glycidyl methacrylate-bisphenol A epoxy diacrylate terpolymer are as follows:

[0014] (1) adding glycidyl methacrylate, trifluoroethyl methacrylate and propyl acetate to deionized water, stirring and reacting at room temperature to obtain solution A;

[0015] (2) adding bisphenol A epoxy diacrylate, propyl acetate and tert-dodecyl mercaptan into deionized water, stirring and reacting at room temperature to obtain solution B;

[0016] (3) adding propyl acetate and azobisisoheptanenitrile to deionized water, stirring and reacting at room temperature to obtain solution C;

[0017] (4) The above solution A, solution B and solution C are stirred together for reaction, and then the reactants are filtered, washed and dried to obtain a terpolymer of trifluoroethyl methacrylate-glycidyl methacrylate-bisphenol A epoxy diacrylate.

[0018] In a further embodiment, the mass ratio of glycidyl methacrylate, trifluoroethyl methacrylate, propyl acetate and deionized water in step (1) is (30-50):(40-60):(10-18):(200-240).

[0019] The mass ratio of bisphenol A epoxy diacrylate, propyl acetate, tert-dodecyl mercaptan and deionized water in step (2) is (50-70): (60-80): (12-20): (180-240).

[0020] The mass ratio of propyl acetate, azobisisoheptanenitrile and deionized water in step (3) is (40-60):(1-3):(100-120).

[0021] The mass ratio of solution A, solution B and solution C in step (4) is (10-16): (8-12): (14-18); the stirring reaction temperature is 70-90°C and the time is 10-12h, and drying refers to drying in an oven at 70-90°C for 1-3h.

[0022] The second object of the present invention is to provide modified nano-cerium oxide prepared by the above preparation method.

[0023] The third object of the present invention is to provide a thermoplastic resin modified material, comprising a thermoplastic resin and the modified nano cerium oxide, wherein the added amount of the modified nano cerium oxide accounts for 20-24% of the total weight of the thermoplastic resin modified material.

[0024] The thermoplastic resin is one of polyethylene (PE), polypropylene (PP), polystyrene (PS), polybutylene terephthalate (PBT), and polyamide 6 (PA6).

[0025] The beneficial effects of the present invention are:

[0026] (1) The present invention uses trifluoroethyl methacrylate-glycidyl methacrylate-bisphenol A epoxy diacrylate ternary polymer to modify the surface of nano-CeO2. Since the ternary polymer is coated on the surface of nano-CeO2, the presence of epoxy groups therein can improve the interfacial compatibility between the thermoplastic resin matrix and the nano-CeO2.

[0027] (2) The modified nano-CeO2 prepared by the present invention has a very small average particle size, which effectively prevents the agglomeration of nano-CeO2 and improves the compatibility of nano-CeO2 with the thermoplastic resin matrix and the dispersibility in the thermoplastic resin matrix.

[0028] (3) Compared with the commercially available nano-cerium oxide-modified thermoplastic resin, the modified nano-cerium oxide-modified thermoplastic resin prepared by the present invention has better physical properties and has great promotion value. DETAILED DESCRIPTION

[0029] In order to make the above-mentioned objects, features and advantages of the invention more obvious and easy to understand, the specific embodiments of the invention are described in detail below.

[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0031] The raw materials used in the following embodiments of the present invention are selected from the following products (but not only this product, other products are also possible, here are just examples):

[0032] PBT (model 2002U), Polyplastics, Japan;

[0033] PP (model Z30S), Maoming Petrochemical;

[0034] PE (model 5070), Panjin Ethylene Industry Company;

[0035] PA6 (model CM1017), Toray, Japan;

[0036] PS (model 350), Guoqiao, Taiwan Province of China;

[0037] Nano CeO2, Wuhu Huatai Chemical;

[0038] Glycidyl methacrylate, Nanjing Rongan Chemical Technology Co., Ltd.;

[0039] Trifluoroethyl methacrylate, Shanghai Haosheng Chemical Technology Co., Ltd.;

[0040] Propyl acetate, Shandong Shenyuan Chemical Co., Ltd.;

[0041] Deionized water, Jinan Hairuibao Chemical Co., Ltd.;

[0042] Bisphenol A epoxy diacrylate, Guangzhou Five Elements Material Technology Co., Ltd.;

[0043] Tert-dodecyl mercaptan, Shanghai Jinghu Chemical Co., Ltd.;

[0044] Azobis(isoheptanonitrile), Zibo Chunwangda Chemical Co., Ltd.;

[0045] Potassium sulfate, Shanghai Huitian Industrial Co., Ltd.;

[0046] Triethylamine, Nanjing Shengqinghe Chemical;

[0047] N,N-Dimethylformamide, Nanjing Shengqinghe Chemical Industry.

[0048] The testing instrument used in the present invention is as follows:

[0049] ZSK30 twin-screw extruder, W&P, Germany;

[0050] JL-1000 tensile testing machine, produced by Guangzhou Guangcai Experimental Instrument Co., Ltd.

[0051] HTL900-T-5B injection molding machine, produced by Haitai Plastic Machinery Co., Ltd.;

[0052] XCJ-500 impact testing machine, produced by Chengde Testing Machine Factory;

[0053] QT-1196 tensile tester, Dongguan Gaotai Testing Instrument Co., Ltd.;

[0054] QD-GJS-B12K high-speed mixer, Beijing Hengaode Instrument Co., Ltd.

[0055] Preparation Example 1

[0056] (1) Weigh 300 g of glycidyl methacrylate, 400 g of trifluoroethyl methacrylate, 100 g of propyl acetate, and 2.0 kg of deionized water, put them into a reaction vessel, and stir them at room temperature for 20 min to obtain solution A;

[0057] (2) Weigh 500 g of bisphenol A epoxy diacrylate, 600 g of propyl acetate, 120 g of tert-dodecyl mercaptan, and 1.8 kg of deionized water, put them into a reaction vessel, and stir them at room temperature for 10 min to obtain solution B;

[0058] (3) Weigh 400 g of propyl acetate, 10 g of azobisisoheptanenitrile, and 1.0 kg of deionized water, put them into a reaction vessel, and stir them at room temperature for 8 min to obtain solution C;

[0059] (4) Weigh 100 g of solution A, 80 g of solution B, and 140 g of solution C, put them into a reaction vessel, stir and react at 70° C. for 10 h, filter, wash, and dry in an oven at 70° C. for 1 h to obtain trifluoroethyl methacrylate-glycidyl methacrylate-bisphenol A epoxy diacrylate ternary polymer M1.

[0060] Example 1

[0061] (1) Weigh 800 g of nano-CeO2, 20 g of terpolymer M1, 1 g of potassium sulfate, and 1 g of triethylamine, put them into a reaction vessel, stir and react at 40°C for 6 h, and obtain solution D;

[0062] (2) Weigh 300 g of solution D and 800 g of N,N-dimethylformamide, put them into a reaction vessel, stir and react at room temperature for 1 h, and obtain solution E;

[0063] (3) Solution E was filtered, washed, and dried in an oven at 60°C for 2 h to obtain modified nano-CeO2P1.

[0064] Application Example 1

[0065] 20 parts of modified nano-CeO2P1 were added to 80 parts of polypropylene (PP), stirred in a high-speed mixer for 10 minutes, and then added to a twin-screw extruder for blending and extrusion to obtain a PP composite material X1.

[0066] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 170°C, the temperature of the second temperature zone is 220°C, the temperature of the third temperature zone is 230°C, the temperature of the fourth temperature zone is 240°C, the temperature of the fifth temperature zone is 240°C, the temperature of the sixth temperature zone is 240°C, the head temperature of the twin-screw extruder is 230°C, and the screw speed is 220r / min.

[0067] Comparative Example 1

[0068] 20 parts of nano-CeO2 were added to 80 parts of polypropylene (PP), stirred in a high-speed mixer for 10 minutes, and then added to a twin-screw extruder for blending and extrusion to obtain a nano-CeO2 / PP composite material D1. The twin-screw extruder was the same as that in Application Example 1.

[0069] The PP composite materials prepared in the above Application Example 1 and Comparative Example 1 were made into strips by an injection molding machine, and the product performance data are shown in the following table:

[0070] Test items Test Standards unit X1 D1 Tensile Strength ASTM D638 MPa 17.8 13.2 Flexural modulus ASTM D790 MPa 1780 1290 Izod impact strength ASTM D256 <![CDATA[kJ / m 2 ]]> 5.7 3.2

[0071] It can be seen from the above table:

[0072] The tensile strength, bending strength and cantilever beam impact strength of X1 are greater than those of D1, which indicates that the mechanical properties of PP modified by adding the modified nano-CeO2 of the present invention are better than those simply adding commercially available nano-CeO2.

[0073] Preparation Example 2

[0074] (1) Weigh 500 g of glycidyl methacrylate, 600 g of trifluoroethyl methacrylate, 180 g of propyl acetate, and 2.4 kg of deionized water, put them into a reaction vessel, and stir them at room temperature for 30 min to obtain solution A;

[0075] (2) Weigh 700 g of bisphenol A epoxy diacrylate, 800 g of propyl acetate, 200 g of tert-dodecyl mercaptan, and 2.4 kg of deionized water, put them into a reaction vessel, stir and react at room temperature for 20 min, and obtain solution B;

[0076] (3) Weigh 600 g of propyl acetate, 30 g of azobisisoheptanenitrile, and 1.2 kg of deionized water, put them into a reaction vessel, and stir them at room temperature for 12 min to obtain solution C;

[0077] (4) Weigh 160 g of solution A, 120 g of solution B, and 180 g of solution C, put them into a reaction vessel, stir and react at 90° C. for 12 h, filter, wash, and dry in an oven at 90° C. for 3 h to obtain trifluoroethyl methacrylate-glycidyl methacrylate-bisphenol A epoxy diacrylate ternary polymer M2.

[0078] Example 2

[0079] (1) Weigh 1.0 kg of nano-CeO2, 60 g of terpolymer M2, 2 g of potassium sulfate, and 2 g of triethylamine, put them into a reaction vessel, stir and react at 60°C for 8 h, and obtain solution D;

[0080] (2) Weigh 400 g of solution D and 1.0 kg of N,N-dimethylformamide, put them into a reaction vessel, and stir them at room temperature for 3 h to obtain solution E.

[0081] (3) Solution E was filtered, washed, and dried in an oven at 80°C for 4 h to obtain modified nano-CeO2P2.

[0082] Application Example 2

[0083] 24 parts of P2 were added to 76 parts of polybutylene terephthalate (PBT), stirred in a high-speed mixer for 10 minutes, and then added to a twin-screw extruder for blending and extrusion to obtain a PBT composite material X2.

[0084] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 200°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 260°C, and the screw speed is 300r / min.

[0085] Comparative Example 2

[0086] 24 parts of nano-CeO2 were added to 76 parts of PBT, stirred in a high-speed mixer for 10 minutes, and then added to a twin-screw extruder for blending and extrusion to obtain a nano-CeO2 / PBT composite material D2. The twin-screw extruder process was the same as that in Application Example 2.

[0087] The PBT composite materials prepared in the above Application Example 2 and Comparative Example 2 were made into strips by an injection molding machine, and the product performance data are shown in the following table:

[0088] Test items Test Standards unit X2 D2 Tensile Strength ASTM D638 MPa 75.3 61.4 Flexural modulus ASTM D790 MPa 3160 2750 Izod impact strength ASTM D256 <![CDATA[kJ / m 2 ]]> 4.9 2.1

[0089] It can be seen from the above table:

[0090] The tensile strength, bending strength and cantilever beam impact strength of X2 are greater than those of D2, which indicates that the mechanical properties of the final modified material obtained by adding the modified nano-CeO2 of the present invention to modified PBT are better than those obtained by simply adding the commercially available nano-CeO2 to modified PBT.

[0091] Preparation Example 3

[0092] (1) Weigh 400 g of glycidyl methacrylate, 500 g of trifluoroethyl methacrylate, 140 g of propyl acetate, and 2.2 kg of deionized water, put them into a reaction vessel, and stir them at room temperature for 25 min to obtain solution A;

[0093] (2) Weigh 600 g of bisphenol A epoxy diacrylate, 700 g of propyl acetate, 160 g of tert-dodecyl mercaptan, and 2.1 kg of deionized water, put them into a reaction vessel, and stir them at room temperature for 15 min to obtain solution B;

[0094] (3) Weigh 500 g of propyl acetate, 20 g of azobisisoheptanenitrile, and 1.1 kg of deionized water, put them into a reaction vessel, and stir them at room temperature for 10 min to obtain solution C;

[0095] (4) Weigh 130 g of solution A, 100 g of solution B, and 160 g of solution C, put them into a reaction vessel, stir and react at 80° C. for 11 h, filter, wash, and dry in an oven at 80° C. for 2 h to obtain trifluoroethyl methacrylate-glycidyl methacrylate-bisphenol A epoxy diacrylate ternary polymer M3.

[0096] Example 3

[0097] (1) Weigh 900 g of nano-CeO2, 40 g of terpolymer M3, 1.5 g of potassium sulfate, and 1.5 g of triethylamine, put them into a reaction vessel, and stir at 50°C for 7 h to obtain solution D;

[0098] (2) Weigh 350 g of solution D and 900 g of N,N-dimethylformamide, put them into a reaction vessel, stir and react at room temperature for 2 h, and obtain solution E;

[0099] (3) Solution E was filtered, washed, and dried in an oven at 70°C for 3 h to obtain modified nano-CeO2P3.

[0100] Application Example 3

[0101] 22 parts of P3 were added to 78 parts of polyethylene (PE), stirred in a high-speed mixer for 10 minutes, and then added to a twin-screw extruder for blending and extrusion to obtain a PE composite material X3.

[0102] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 120°C, the temperature of the second temperature zone is 180°C, the temperature of the third temperature zone is 180°C, the temperature of the fourth temperature zone is 180°C, the temperature of the fifth temperature zone is 180°C, the temperature of the sixth temperature zone is 180°C, the head temperature of the twin-screw extruder is 180°C, and the screw speed is 300r / min.

[0103] Comparative Example 3

[0104] 22 parts of nano-CeO2 were added to 78 parts of PE, stirred in a high-speed mixer for 10 minutes, and then added to a twin-screw extruder for blending and extrusion to obtain a nano-CeO2 / PE composite material D3.

[0105] The PE composite materials prepared in the above Application Example 3 and Comparative Example 3 were made into strips by an injection molding machine, and the product performance data are shown in the following table:

[0106]

[0107]

[0108] It can be seen from the above table:

[0109] The tensile strength, bending strength and cantilever beam impact strength of X3 are greater than those of D3, which indicates that the physical properties of PE modified by adding the modified nano-CeO2 of the present invention are better than those of PE modified by simply adding commercially available nano-CeO2.

[0110] Preparation Example 4

[0111] (1) Weigh 350 g of glycidyl methacrylate, 420 g of trifluoroethyl methacrylate, 170 g of propyl acetate, and 2.3 kg of deionized water, put them into a reaction vessel, stir and react at room temperature for 22 minutes, and obtain solution A;

[0112] (2) Weigh 560 g of bisphenol A epoxy diacrylate, 610 g of propyl acetate, 170 g of tert-dodecyl mercaptan, and 2.3 kg of deionized water, put them into a reaction vessel, stir and react at room temperature for 19 minutes, and obtain solution B;

[0113] (3) Weigh 480 g of propyl acetate, 25 g of azobisisoheptanenitrile, and 1.2 kg of deionized water, put them into a reaction vessel, stir and react at room temperature for 9 minutes to obtain solution C;

[0114] (4) Weigh 110 g of solution A, 110 g of solution B, and 170 g of solution C, put them into a reaction vessel, stir and react at 75° C. for 11 h, filter, wash, and dry in an oven at 75° C. for 2 h to obtain trifluoroethyl methacrylate-glycidyl methacrylate-bisphenol A epoxy diacrylate ternary polymer M4.

[0115] Example 4

[0116] (1) Weigh 950 g of nano-CeO2, 50 g of terpolymer M4, 2 g of potassium sulfate, and 2 g of triethylamine, place them in a reaction vessel, stir and react at 45°C for 6 h, and obtain solution D;

[0117] (2) Weigh 380 g of solution D and 1.0 kg of N,N-dimethylformamide, put them into a reaction vessel and stir them for 1 h at room temperature to obtain solution E;

[0118] (3) Solution E was filtered, washed, and dried in an oven at 65°C for 2 h to obtain modified nano-CeO2P4.

[0119] Application Example 4

[0120] 21 parts of P4 were added to 79 parts of polyamide 6 (PA6), stirred in a high-speed mixer for 10 minutes, and then added to a twin-screw extruder for blending and extrusion to obtain a PA6 composite material X4.

[0121] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 130°C, the temperature of the second temperature zone is 260°C, the temperature of the third temperature zone is 260°C, the temperature of the fourth temperature zone is 260°C, the temperature of the fifth temperature zone is 260°C, the temperature of the sixth temperature zone is 260°C, the head temperature of the twin-screw extruder is 250°C, and the screw speed is 320r / min.

[0122] Comparative Example 4

[0123] 21 parts of nano-CeO2 were added to 79 parts of PA6, stirred in a high-speed mixer for 10 minutes, and then added to a twin-screw extruder for blending and extrusion to obtain a nano-CeO2 / PA6 composite material D4.

[0124] The PA6 composite materials prepared in the above Application Example 4 and Comparative Example 4 were made into strips by an injection molding machine, and the product performance data are shown in the following table:

[0125] Test items Test Standards unit X4 D4 Tensile Strength ASTM D638 MPa 75.3 67.4 Flexural modulus ASTM D790 MPa 3180 2710 Izod impact strength ASTM D256 <![CDATA[kJ / m 2 ]]> 7.5 4.4

[0126] It can be seen from the above table:

[0127] The tensile strength, bending strength and cantilever beam impact strength of X4 are greater than those of D4, which indicates that the physical properties of PA6 modified by adding the modified nano-CeO2 of the present invention are better than those simply adding commercially available nano-CeO2.

[0128] Preparation Example 5

[0129] (1) Weigh 370 g of glycidyl methacrylate, 580 g of trifluoroethyl methacrylate, 170 g of propyl acetate, and 2.0 kg of deionized water, put them into a reaction vessel, stir and react at room temperature for 22 minutes, and obtain solution A;

[0130] (2) Weigh 680 g of bisphenol A epoxy diacrylate, 690 g of propyl acetate, 190 g of tert-dodecyl mercaptan, and 2.4 kg of deionized water, put them into a reaction vessel, stir and react at room temperature for 11 minutes, and obtain solution B;

[0131] (3) Weigh 550 g of propyl acetate, 28 g of azobisisoheptanenitrile, and 1.1 kg of deionized water, put them into a reaction vessel, stir and react at room temperature for 11 min to obtain solution C;

[0132] (4) Weigh 150 g of solution A, 110 g of solution B, and 170 g of solution C, put them into a reaction vessel, stir and react at 75° C. for 11 h, filter, wash, and dry in an oven at 75° C. for 1 h to obtain trifluoroethyl methacrylate-glycidyl methacrylate-bisphenol A epoxy diacrylate terpolymer M5.

[0133] Example 5

[0134] (1) Weigh 910 g of nano-CeO2, 50 g of terpolymer M5, 1 g of potassium sulfate, and 1 g of triethylamine, place them in a reaction vessel, stir and react at 48°C for 7 h, and obtain solution D;

[0135] (2) Weigh 330 g of solution D and 820 g of N,N-dimethylformamide, put them into a reaction vessel, stir and react at room temperature for 1 h, and obtain solution E;

[0136] (3) Solution E was filtered, washed, and dried in an oven at 65°C for 2 h to obtain modified nano-CeO2P5.

[0137] Application Example 5

[0138] 22 parts of P5 were added to 78 parts of styrene (PS), stirred in a high-speed mixer for 10 minutes, and then added to a twin-screw extruder for blending and extrusion to obtain a PS composite material X5.

[0139] Among them, the twin-screw extruder includes six temperature zones arranged in sequence, the temperature of the first temperature zone is 160°C, the temperature of the second temperature zone is 200°C, the temperature of the third temperature zone is 200°C, the temperature of the fourth temperature zone is 200°C, the temperature of the fifth temperature zone is 200°C, the temperature of the sixth temperature zone is 200°C, the head temperature of the twin-screw extruder is 200°C, and the screw speed is 280r / min.

[0140] Comparative Example 5

[0141] 22 parts of nano-CeO2 were added to 78 parts of PS, stirred in a high-speed mixer for 10 minutes, and then added to a twin-screw extruder for blending and extrusion to obtain a nano-CeO2 / PS composite material D5.

[0142] The PS composite materials prepared in the above-mentioned Application Example 5 and Comparative Example 5 were made into strips by an injection molding machine, and the product performance data are shown in the following table:

[0143] Test items Test Standards unit X5 D5 Tensile Strength ASTM D638 MPa 53 46 Flexural modulus ASTM D790 MPa 3850 3420 Izod impact strength ASTM D256 <![CDATA[kJ / m 2 ]]> 5.3 3.7

[0144] It can be seen from the above table:

[0145] The tensile strength, bending strength and cantilever beam impact strength of X5 are greater than those of D5, which indicates that the physical properties of PS modified by adding the modified nano-CeO2 of the present invention are better than those of PS modified by simply adding commercially available nano-CeO2.

[0146] The invention describes a modified nano CeO2 and a preparation method thereof, and the physical properties of the prepared thermoplastic resin material are also improved to a certain extent, which greatly expands the application field of thermoplastic resin composite materials and has very important significance.

[0147] The above disclosures are only a few specific embodiments of the present application, but the present application is not limited thereto, and any changes that can be conceived by those skilled in the art should fall within the protection scope of the present application.

Claims

1. A method for preparing modified nano cerium oxide, characterized in that: The steps include: (1) stirring and reacting nano-cerium oxide, a terpolymer and a catalyst to obtain a solution D, wherein the terpolymer is a terpolymer of trifluoroethyl methacrylate-glycidyl methacrylate-bisphenol A epoxy diacrylate; (2) stirring solution D and N,N-dimethylformamide at room temperature to obtain solution E; (3) Filter, wash and dry the solution E to obtain modified nano-cerium oxide.

2. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of the nano-cerium oxide, the terpolymer and the catalyst is (80-100): (2-6): (0.2-0.4).

3. The preparation method according to claim 1, characterized in that: In step (1), the catalyst is potassium sulfate and triethylamine, and the mass ratio of the two is 1:1; the stirring reaction temperature is 40-60° C. and the time is 6-8 hours.

4. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of solution D to N,N-dimethylformamide is (30-40):(80-100); and the stirring reaction time is 1-3h. The drying in step (3) refers to drying in an oven at 60-80°C for 2-4 hours.

5. The preparation method according to claim 1, characterized in that: The preparation steps of the trifluoroethyl methacrylate-glycidyl methacrylate-bisphenol A epoxy diacrylate terpolymer are as follows: (1) adding glycidyl methacrylate, trifluoroethyl methacrylate and propyl acetate to deionized water, stirring and reacting at room temperature to obtain solution A; (2) adding bisphenol A epoxy diacrylate, propyl acetate and tert-dodecyl mercaptan into deionized water, stirring and reacting at room temperature to obtain solution B; (3) adding propyl acetate and azobisisoheptanenitrile to deionized water, stirring and reacting at room temperature to obtain solution C; (4) The above solution A, solution B and solution C are stirred together for reaction, and then the reactants are filtered, washed and dried to obtain a terpolymer of trifluoroethyl methacrylate-glycidyl methacrylate-bisphenol A epoxy diacrylate.

6. The preparation method according to claim 5, characterized in that: The mass ratio of glycidyl methacrylate, trifluoroethyl methacrylate, propyl acetate and deionized water in step (1) is (30-50):(40-60):(10-18):(200-240).

7. The preparation method according to claim 5, characterized in that: The mass ratio of bisphenol A epoxy diacrylate, propyl acetate, tert-dodecyl mercaptan and deionized water in step (2) is (50-70): (60-80): (12-20): (180-240); The mass ratio of propyl acetate, azobisisoheptanenitrile and deionized water in step (3) is (40-60):(1-3):(100-120).

8. The preparation method according to claim 5, characterized in that: The mass ratio of solution A, solution B and solution C in step (4) is (10-16): (8-12): (14-18); the stirring reaction temperature is 70-90°C and the time is 10-12h, and drying refers to drying in an oven at 70-90°C for 1-3h.

9. The modified nano cerium oxide prepared by the preparation method according to any one of claims 1 to 8.

10. A thermoplastic resin modified material, characterized in that: The invention comprises a thermoplastic resin and the modified nano cerium oxide as claimed in claim 9, wherein the added amount of the modified nano cerium oxide accounts for 20-24% of the total weight of the thermoplastic resin modified material.